Clinical Criteria and Operative Complications of Complicated Cholangitis - Quirino Esteves, Thaís Augusta; Thiago Mendonça Estrela Nascente,; Alexônia Divina Ramos Padilha,; Ana Clara Linhares Volpp,; Luis Felipe Amaral Bueno,; Thearley Marques de Queiroz,; Camila Oliveira Câmara Ferreira,; Andreza Maiclem Cruz Ramos,; Milena Morini Marques,; Isabela Machado de Souza,; Clara Arantes Vasconcelos,; Camylla Silva Gomes Paulino,; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Complicated cholangitis is a severe bacterial infection of the bile ducts that often occurs in patients with biliary obstruction. The condition is characterized by a clinical presentation of fever, abdominal pain, and jaundice, frequently exacerbated by complications such as sepsis and liver failure. Cholangitis can result from bile duct stones, strictures, or other obstructions that impair bile flow, leading to infection and inflammation of the ducts. Understanding the clinical criteria and associated complications is crucial for appropriate management and reduction of morbidity. Objective: To evaluate the clinical criteria most commonly used in the diagnosis and management of complicated cholangitis and to identify the operative complications associated with this condition. Methodology: The review was conducted in accordance with the PRISMA checklist, utilizing the PubMed, Scielo, and Web of Science databases. Articles published in the last 10 years were selected using five descriptors: “complicated cholangitis,” “diagnosis,” “operative complications,” “clinical management,” and “treatment.” The search aimed to identify relevant studies addressing the clinical criteria and complications associated with complicated cholangitis. Inclusion criteria were: Studies describing clinical criteria and operative complications of complicated cholangitis; Peer-reviewed articles published in the last 10 years; Clinical studies with primary data on the management of complicated cholangitis. Exclusion criteria were: Articles outside the established time frame; Studies not specifically focused on complicated cholangitis; Publications not available in full text or not accessible in English, Spanish, or Portuguese. Results: The review revealed that fundamental clinical criteria for diagnosing complicated cholangitis include Charcot’s triad (fever, abdominal pain, and jaundice) and signs of systemic inflammation. Commonly associated operative complications include sepsis, hepatic abscesses, and liver failure. The most effective diagnostic methods were endoscopic retrograde cholangiopancreatography (ERCP) and abdominal ultrasound. Early intervention and appropriate management of complications were identified as critical factors for improving prognosis. Conclusion: Clinical criteria for identifying complicated cholangitis are well established, but the complexity of the condition and its potential operative complications necessitate a detailed and well-coordinated approach. The systematic review emphasized the importance of early identification and effective treatment to minimize severe complications and improve clinical outcomes. Implementing evidence-based management strategies is essential to optimize treatment and reduce morbidity associated with complicated cholangitis.